Disambiguating Geographic Names in a Historical Digital Library - Smith, David A.; Crane, Gregory (Tufts Archival Research Center, 2005)
Geographic interfaces provide natural, scalable visualizations for many digital library collections, but the wide range of data in digital libraries presents some particular problems for identifying and disambiguating place names. We describe the toponym-disambiguation system in the Perseus digital library and evaluate its performance. Name categorization varies significantly among different types of documents, but toponym disambiguation performs at a high level of precision and recall with a gazetteer an order of magnitude larger than most other applications.